A comparative study on the clinical success of restorations with MTA and gray Portland cement in permanent molar perforations - M Zarei; M Sedigh; M Bidar (Isfahan University of Medical Sciences, 2010)
Introduction: A large number of materials have so far been applied to restore tooth perforations. Gray MTA is now the material of choice for such purpose. However Portland cement with a lower price and high structural similarity to MTA can be a suitable substituent. The aim of this study was to compare the success of mechanical perforation restorations with Portland cement and MTA.Materials and Methods: in this comparative clinical trial, 30 perforations in the teeth of 30 patients were treated at Mashhad Dental School Clinic using either MTA or Portland cement type IV which was opaqued using 20% Bismuth Oxide. The patients were invited for clinical and radiological follow-up 3 and 6 months later. Two endodontists separately evaluated the success of restorations on the basis of X-ray and clinical examination. Chi square test was used for statistical analysis of the collected data.Results: In 3 and 6 month interval follow up just one case of failure was recorded in both MTA and Portland cement groups. No significant difference was found between the two study groups (p value = 1).Conclusion: Portland cement type IV can replace gray MTA in restoration of dental perforations where aesthetic aspects are not of much concern. Key words: Clinical trial, Portland cement, Root perforation, MTA, Permanent molar.